2019
DOI: 10.1073/pnas.1902148116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular codes and in vitro generation of hypocretin and melanin concentrating hormone neurons

Abstract: Hypocretin/orexin (HCRT) and melanin concentrating hormone (MCH) neuropeptides are exclusively produced by the lateral hypothalamus and play important roles in sleep, metabolism, reward, and motivation. Loss of HCRT (ligands or receptors) causes the sleep disorder narcolepsy with cataplexy in humans and in animal models. How these neuropeptides are produced and involved in diverse functions remain unknown. Here, we developed methods to sort and purify HCRT and MCH neurons from the mouse late embryonic hypothal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…The increase in Snord116 in mice with depletion of OX neurons is probably a compensatory mechanism. Our conclusions are supported by a recent study [48] that described the role of Peg3 in the development and expression of OX and MCH neurons. Our study demonstrates for the first time that Peg3 is able to bind OX promotors by increasing the expression of OX.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in Snord116 in mice with depletion of OX neurons is probably a compensatory mechanism. Our conclusions are supported by a recent study [48] that described the role of Peg3 in the development and expression of OX and MCH neurons. Our study demonstrates for the first time that Peg3 is able to bind OX promotors by increasing the expression of OX.…”
Section: Discussionsupporting
confidence: 90%
“…Peg3 binds to DNA based on its multiple zinc finger motifs and nuclear localization [27,28]. Interestingly, a recent study found an association between Peg3 and OX expression [29]. However, whether Peg3 is able to bind and regulate the expression of OX in living mice remains unclear.…”
Section: Peg3mentioning
confidence: 99%
“…This altered modulation between cortical states, behavior, and subcortical neuronal activity in Snord116-deleted mice is accompanied by a loss of OX-expressing neurons in the LH. We also report, for the first time to our knowledge, a link between Snord116 and a different paternally imprinted gene, Peg3, which has been recently associated with the control of the hypothalamic OX neuromodulatory system (16).…”
Section: Introductionmentioning
confidence: 72%
“…PEG3 binds to DNA based on its multiple zinc finger motifs and nuclear localization (31,32). Interestingly, a recent study found an association between Peg3 and OX expression (16). However, whether PEG3 is able to bind and regulate the expression of OX in living mice remains unclear.…”
Section: Loss Of Paternal Snord116 Alters Neuronal Dynamics In the Lhmentioning
confidence: 99%
“…Ghrh neuron clusters were isolated at the whole-brain level and whole-hypothalamic level and was identified in the POA/ARC but significantly the dopaminergic Ghrh/Gal cluster was identified in both the dopamine-wide and arcuate nucleus datasets. Finally, other neural populations were identified which have previously been associated with imprinted genes including the Hcrt population of the LHA (Seifinejad et al, 2019) identified at the whole brain and LHA level, and the Pomc neurons of the ARC (Cassidy & Charalambous, 2018) identified at the arcuate nucleus level.…”
Section: Discussionmentioning
confidence: 99%